A comparative life cycle assessment of lithium-ion and lead-acid batteries for grid energy storage. (15th July 2022) - Yudhistira, Ryutaka; Khatiwada, Dilip; Sanchez, Fernando
Abstract: Lithium-ion battery technology is one of the innovations gaining interest in utility-scale energy storage. However, there is a lack of scientific studies about its environmental performance. This study aims to evaluate the environmental impacts of lithium-ion batteries and conventional lead-acid batteries for stationary grid storage applications using life cycle assessment. The cradle-to-grave life cycle study shows that the environmental impacts of the lead-acid battery measured in per "kWh energy delivered" are: 2 kg CO2eq (climate change), 33 MJ (fossil fuel use), 0.02 mol H + eq (acidification potential), 10 −7 disease incidence (PM2.5 emission), and 8 × 10 −4  kg Sbeq (minerals and metals use). The nickel cobalt aluminum battery is the best performer for climate change and resource use (fossil fuels) among the analysed lithium-ion batteries, with 45% less impact. The nickel cobalt manganese battery performs better for the acidification potential and particulate matter impact categories, with 67% and 50% better performance than lead-acid. The lithium iron phosphate battery is the best performer at 94% less impact for the minerals and metals resource use category. The use stage electricity and battery cell manufacturing processes have the highest contribution for the most impact categories. The sensitivity analysis shows that the use-phase environmental impact decreases with an increase in renewable energy contribution in the use phase. The lithium-ion batteries have fewer environmental impacts than lead-acid batteries for the observed environmental impact categories. The study can be used as a reference to decide how to substitute lead-acid batteries with lithium-ion batteries for grid energy storage applications. Graphical abstract: Image 1 Highlights: Life cycle assessment of lithium-ion and lead-acid batteries is performed. Three lithium-ion battery chemistries (NCA, NMC, and LFP) are analysed. NCA battery performs better for climate change and resource utilisation. NMC battery is good in terms of acidification potential and particular matter. The operational phase accounts for most environmental impacts.